Implementation of Certainty Factor Method on Problematic Student Counseling Guidance Expert System - Zilullah Nazir Hadi; Dyah Susilowati; Hairani Hairani; Muhammad Innuddin (Prodi Ilmu Komputer Universitas Bumigora, 2021)
The main thing in the development of education is the quality of education. One of the determinants of the quality of education is counseling guidance. The problem so far is that most students who have problems feel embarrassed in doing counseling directly to the BK teacher and usually consult with their friends so that they cannot solve the problems they face. This makes it difficult for BK teachers to deal with student problems, so we need a system that can help and solve problems experienced by students. The purpose of this study is to design an expert system that overcomes the problems suffered by students using the certainty factor method that can provide solutions based on the types of problems suffered by the students. The expert system development methodology in this study uses the waterfall methodology which consists of needs analysis, design, coding, and testing. The result of this research is in the form of an expert system application for counseling problem students who apply a web-based certainty factor method that can make it easier for students to find out the types of problems they face based on the problems symptoms entered. This study concludes that the expert system application that was built has a good level of convenience based on the results of usability testing using the SUS (System Usability Scale) method of 76.5%.